Enhancing artistic skills of gifted preschoolers through discipline-based art education - Defeo, Charo Marie V. (2009)
A comprehensive art education promotes the attainment of knowledge, understanding, and skills that contribute to the child's intellectual, social, emotional, and physical development. This study explored the possibility of improving art skills of gifted preschoolers through a Discipline-Based Art Education Approach. A single group design conducted at UPIS for 3 week every Monday was used for this study with Kindergarten children as participants. There was a significant improvement in the artistic skills of gifted preschoolers using the DBAE approach particularly in their fluency and originality. They also improved in their Art Criticism, which means they developed their art vocabulary and ability to categorize works of art. To display more improvement in their artistic skills, the time frame for the exposure to DBAE may be extended.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Gifted children -- Philippines -- Quezon City; Art -- Study and teaching (Preschool) -- Philippines; Education, Preschool -- Philippines -- Quezon City; Creative ability in children -- Philippines -- Quezon City